1995
DOI: 10.1042/bj3060161
|View full text |Cite
|
Sign up to set email alerts
|

Expression and alternative splicing of the cytochrome P-450 CYP2A7

Abstract: In order to investigate the relative levels of expression of human cytochrome P-450 (P-450) CYP2A genes and determine how this relates to polymorphism in coumarin hydroxylase activity, cDNA clones for members of the CYP2A gene family were isolated. These clones were CYP2A6, CYP2A7 and an alternatively spliced version of CYP2A7 (CYP2A7AS). The latter clone was missing exon 2, but contained a 10 bp segment of intron 1. Translation of CYP2A7AS resulted in an in-frame deletion of 51 amino acids. The expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…6 CYP2A7 has been shown to not incorporate heme and to be functionally inactive. 2,7 There are genetic polymorphisms in the CYP2A6 gene. In addition to a variety of single nucleotide polymorphism (SNP)s, several alleles that are produced by crossover with the CYP2A7 gene are known to exist.…”
Section: Introductionmentioning
confidence: 99%
“…6 CYP2A7 has been shown to not incorporate heme and to be functionally inactive. 2,7 There are genetic polymorphisms in the CYP2A6 gene. In addition to a variety of single nucleotide polymorphism (SNP)s, several alleles that are produced by crossover with the CYP2A7 gene are known to exist.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered as an important factor in regulating the enzyme level and may be the cause for tissue-specific variation. 30 Several studies show that alternative splicing occurs frequently in human cancers cells, e.g., breast and ovarian cancer although the cause of the increase is not known. 31,32 Alternative splicing has been suggested to have the potential as a diagnostic marker for cancer.…”
Section: Treatment With 25(oh)d Does Not Modulate Growth Of Melanoma mentioning
confidence: 99%
“…Human CYP2A gene subfamily has three members: CYP2A6, CYP2A7, and CYP2A13 (Su et al, 2000). Whereas CYP2A6 is a major human enzyme for the metabolism of coumarin and nicotine, CYP2A7 has no catalytic activity (Ding et al, 1995). Our previous work demonstrated that CYP2A13 has the highest catalytic efficiency, among all the known human P450 enzymes, in the metabolic activation of a major tobaccospecific carcinogen, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) (Su et al, 2000;He et al, 2004).…”
mentioning
confidence: 99%